Are climate and security policies coherent and integrated in Guatemala? A policy coherence analysis factsheet - Schapendonk, Frans; Scartozzi, Cesare; Madurga Lopez, Ignacio M.; Salma, Kadry; Pacillo, Grazia; Läderach, Peter R.D. (2023)
This fact sheet assesses the coherence and climate security-sensitivity of policy and strategy documents extracted from sectors relevant to the climate, peace, and security nexus at both the national level in Guatemala and regional level across the Central American Dry Corridor.